THE UPPER CAMBRIAN OF THE CHOPKO RIVER SECTION, NORILSK REGION, NORTHWESTERN SIBERIAN PLATFORM: STRATIGRAPHY AND TRILOBITES - Varlamov A.I.; Pak K.L.; Rosova A.V. (My University, 2006)
The section that serves as a reference section for the upper Middle-Upper Cambrian in the Norilsk Region is studied; regularities in the distribution and succession of lithological varieties of rocks and facial types are established; and intervals representing settings at the base of the outer shelf slope, on the upper shelf slope, and on the shallow-water carbonate platform are recognized. Based on the study of trilobites, ten biostratigraphic units are recognized. Thirty-seven trilobite species are described. The biostratigraphic scheme developed by the authors is correlated with the main world sections.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская